SISTEM PRESENSI DENGAN METODE SIDIK JARI MENGGUNAKAN SENSOR FINGERPRINT DENGAN TAMPILAN PADA PC - Triandes Sinaga (Saintia Fisika, 2013)
ABSTRACT Using Presence system manually usually have many disadvantages such as inimitable. To avoid these conditions, this study used electronically extremely difficult to replicate. The purpose of this is to facilitate peneletian a system Presence To realize these objectives in this study utilized the fingerprint sensor, fingerprint analysis method in which to use the fingerprint pegenalan filtergabor. Sampel approach in this study was conducted to 10 respondents, each with each respondent fingerprint scan data taken by 8 scaning , which varied from the angle (). Based on the analysis of data obtained by the obtained results of 8 respondents stated the same (match) and 2 respondents are not the same (not found) for the angle . So with this conclusion Presence in electronic systems with fingerprint method for use as a Presence system. Keywords :fingerprint, presensi, verifikasi, biometrica